MOTIVASI SEBAGAI PENENTU PERENCANAAN KEUANGAN (SUATU STUDI PUSTAKA) - Sina, Peter Garlans (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 9 No 1 (2014), 2014)
ABSTRACT The aim of this research was to help a family and every household to make financial planning immediately in order to achieve prosperity and not to postpone financial planning. Those who have high motivation tend to stay motivated in trying to fulfill financial freedom. Therefore, it can be started by fulfilling basic needs such as the realization of basic financial transaction, and up to controlling personal finance to the highest need which is the management of personal finance. Keywords :   financial planning, financial transaction, motivation, personal finance